Ureteroinguinal Herniation with Consecutive Ureteral Stricture in a 2-Month-Old Infant: Case Report - Delgado-Miguel, Carlos; Muñoz-Serrano, Antonio Jesus; Aguado, Pablo; Fuentes, Ennio; Díez, Ricardo (European Journal of Pediatric Surgery Reports, 2024)
Inguinal herniation of ureter is an uncommon finding among children, with scarce reported cases in the literature to date, that can potentially lead to obstructive uropathy. We report a case of ureteroinguinal herniation discovered during an inguinal hernia repair in a patient with antenatally ultrasound finding of hydronephrosis. A 2-month-old infant with antenatal left hydronephrosis presented with left inguinal mass. Preoperative ultrasound showed an anechoic tubular image producing a mass effect on the left testicle, with suspected bladder herniation and/or dilated ureter toward the inguinal canal. An open surgical inguinal exploration was performed, where the left inguinal canal revealed a peritoneal sac and sliding of the dilated left ureter behind the sac, with a significant change in diameter, corresponding to the paraperitoneal variant of ureteroinguinal herniation. Ligation of the sac and replacement of the ureter into the retroperitoneum were performed, with improvement in the hydronephrosis observed on the ultrasound 1 month after the intervention. However, 6 months later, hydronephrosis worsening as well as the obstructive pattern observed in the diuretic renogram required removal of the stenotic ureteral segment and reimplantation of the healthy proximal segment in the bladder by open approach (Cohen's reimplantation). Follow-up ultrasound of the renal tract showed no dilatation of the upper renal tract and the renal function tests were normal. Currently, the patient is 2 years old and he remains asymptomatic. In conclusion, signs of ureteral obstruction such as hydronephrosis in patients with inguinal herniation may suggest the possibility of an ureteroinguinal hernia. Preoperative diagnostic suspicion is essential.
Keywords: ureteroinguinal hernia; herniation of the ureter; hydronephrosis; upper urinary tract obstruction